Drying of malt residues in a solar greenhouse and in a fixed bed solar dryer (Research, Society and Development, 2020)
The brewing industries generate large amounts of barley residues (RM), which can be used as animal feed. However, the high moisture of RM can lead to losses due to mold or fermentation. In this context, solar drying can be an advantageous operation, as it will favor storage and transportation, while it keeps the waste nutritional quality. Thus, the aim of this work was to study the drying of RM using two equipments: a solar greenhouse and a fixed bed solar dryer. Initially, a study of the drying kinetics was performed at different temperatures, obtaining the Page model as the one that best represents the RM drying kinetics. In the solar drying tests, it was possible to determine the influence of factors such as solar radiation and wind speed on the temperatures obtained, as well as on the drying rate in both equipments. Computational fluid dynamics analysis of the fixed bed dryer showed the best way to feed air into the dryer, which favors drying. However, the solar greenhouse proved to be more efficient, promoting a more homogeneous drying of the material.